TINGKAT KEPUASAN PENGUNJUNG TERHADAP KUALITAS PELAYANAN DAERAH WISATA PUNCAK TEMBOAN TOMOHON - Ellen Grace Tangkere; Lorraine W. Th. Sondak (Sam Ratulangi University, 2017)
The purpose of this study is (1) to measure the level of visitor satisfaction of services in tourism so it can improve or develop the quality of services, (2) identify the advantages and disadvantages of what should be improved or developed to increase the number of visitors at the Heritage Temboan Peak. The study was conducted in the village of Rurukan Tomohon, Village of East Tomohon, Tomohon. The research was conducted during 2016. The primary and secondary data used in this study. Primary data obtained through interviews and direct observation. Interviews conducted using questionnaires that question and the answer has been determined and is given a score. The secondary data obtained from the study of literature in the form of literature, written sources has relevance to this study.Ssampling slection in this study using purposive sampling method. The number of samples in this study were 50 respondents. The analytical method used is the Importance Performance Analysis (IPA) test Validity and Reliability of the variables to be measured. This study found: (1) In general visitor attractions highlight Temboan already satisfied with the quality of services provided by Peak Temboan operators ie at a rate of 75.59%; (2) The service quality indicators which have a high interest rate with a low performance and get into the top priority category for increased need to receive special attention from the manager. The indicator is building a good physical facilities and have charm, cleanliness in environmental tourism, cleanliness of toilets is in the area attractions and the attitude of the staf (friendly, courteous and smiling).